Hotel Impossible. Issue 2 (August 2020) - Kinsella, John
Abstract : Hotel Impossible is the puzzle-world of global capital Pilgrim enters looking for comfort, discovering instead various trials and tribulations on his way through an unresolvable Hell of Whiteworld. As it spreads and occupies the planet, a super-charged colonialism of the now, there's a paddock in the Western Australian Wheatbelt where Sister is waiting, keeping life going as they knew it, but it was always a different kind of life, out of keeping with the conservative rural community around it, a community with its corruptions and invasiveness. Discovering purpose in resisting corruption, Pilgrim decodes his way through the hotel via CERN and Lake Geneva, arriving back 'home' to confront the offices of colonial mining corruption. Bunyan's The Pilgrim's Progress is a de-map in a world of constant remapping and overlays, and Escher and Penrose are clues to possible solutions, but in the end only the land itself and truths outside colonialism can offer any way through without ongoing acts of appropriation, cultural-theft, and the deceptions of 'fictionalising' reality.